En Tunisie, le golfe de Gabes 1888 - Servonnet, Jean; Lafitte (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Monuments – Djerba; Récits de voyage – Djerba; Sidi Garus; mosquée (Haddada; Djerba); Sidi Jmur; mosquée (El Groo; Djerba)

Monographie de l’île de Djerba - Brulard, Armand (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Monuments – Djerba; Récits de voyage – Djerba; Sidi Abd Allah; mosquée (Mezrane; Djerba); Sidi Jmur; mosquée (El Groo; Djerba); Tâjdît; Mosquée (Fâtû; Djerba)

Les installations militaires et la défense des côtes tunisiennes de la période moderne (16ème au 19ème s.) - Djalloul, Neji (Université Paris 4, 1982)
Keywords: Monuments – Djerba

Entre la disparition et la survie: le métier de "Dallâl" à Tunis - Glasman, Wladimir (Revue de l'Institut des Belles Lettres Arabes, 1982)
on a Jerban in the Sūq al-Liffa and on the (Ibāḍī) Masjid al-Hintātī there.* On the (decline of the number of) professional hawkers in the markets of Tunis, taking as an example Mohammed Zakri, born at Jerba around 1910, who became a Dallāl in the Sūq al-Liffa in the Medina of Tunis, a domain more or less reserved for Jerban merchants in woolen cloths. The Masjid al-Hintātī is in front of nr. 79 of this Sūq. I visited the mosque end of June 1972. Entering from the Sūq al-Liffa by a staircase, at the first floor to the left there were two rooms, three showers and three toilets; to the right there were two rooms and a kitchen. The mosque was on the second floor (c. 20x16 m.); some three to five years before a courtyard and three rooms had been added to the mosque. Jaʿbīrī 1975, 259: Sūq al-Hintātī nr. 84.
Keywords: Hintati; mosquée al- (Tunis); Monuments – Djerba